Devolatilization of millimeter-sized biomass particles at high temperatures and heating rates. Part 1: Experimental methods and results. (15th December 2018) - Remacha, M. Pilar; Jiménez, Santiago; Ballester, Javier
Highlights: Devolatilization of biomass at severe conditions is experimentally characterized. Biomass particles of several millimeters are considered. Volatile release rates were estimated via flame size monitoring of flame. Fine thermocouples were used to record the intraparticle temperature history. Heat conduction along the wires may introduce important deviations on the readings. Abstract: In the framework of a general research on biomass combustion, this paper presents and discusses the experimental techniques developed to analyze the heating, drying and devolatilization of biomass particles of few millimeters, a size range scarcely studied in the past. Individual particles were suspended in a stream of hot gases generated by a Flat Flame Burner, with controlled temperature and composition. The evolution of their morphology was monitored by time-lapse photography; additionally, an estimate of the instantaneous volatile release rate was derived from the picture series based on the size of the volatile shell flame. The temperature inside the particles (3–15 mm in diameter) was measured with pairs of fine wire thermocouples located at the particle's center and near its surface. The systematic error associated to this technique (deviations up to 300 K in relation to the actual particle temperature), due to the intense heat transfer along the metal wires, was evaluated experimentally and modeled; the agreement found in the comparison allowed for establishing a procedure to correct those signals and thus adequately evaluate the thermal gradients within the particles. A subsequent comparison of the experimental results (evolution of size, shape, internal temperature and temperature gradients, volatile release rate in a variety of conditions) with simulations performed with models which alternatively consider or neglect internal gradients is presented in a separate paper [21].